Dynamics of mouse-like rodent communities in anthropogenically disturbed territories of the Southeast of Western Siberia (Kemerovo Region, Russia) - Ilyashenko, V. B.; Luchnikova, E. M.; Danilov, V. N.; Kovalevsky, A. V.; Zubko, K. S. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2020)
The research was designed to study the dynamics of mouse-like rodent communities in the area of self-organized vegetation, which had undergone clear-cut deforestation. The research is based on the results of continuous monitoring conducted from 1978 to 2018. Pitfall traps were the key method of catching small mammals throughout the monitoring period.We used Simpson’s Diversity Index to quantify species diversity. The community similarity was evaluated by shares of species through Czekanowski-Sørensen Index. The studies were carried out in the vicinity of the biological station Azhendarovo (54 ° 45ʹ N, 87 ° 01ʹ E) located on the territory of the Kuznetsk-Salair mountain region, in the area where forest-steppe of the Kuznetsk Hollow changes to dark coniferous taiga on the foothills of the Kuznetsk Alatau. The results of the studies showed that natural primeval communities of the taiga zone before deforestation were characterized by a multidominant structure. After the deforestation, the structure changed. The composition of dominant species in the recovering areas of cut-down taiga began to approach to the original state 40 years after the deforestation. Meadow communities followed the path of transformation, having no analogs in the initial period and were characterized by a significant amount of ruderal vegetation.